Complex-mass scheme and effective field theory - Gegelia Jambul (EPJ Web of Conferences, 2014)
The complex-mass scheme applied to hadronic effective field theory is briefly introduced. Some conceptual issues and the application to the calculation of the one-loop corrections to the ρ-meson magnetic moment are discussed.